Direct characterization of graphene doping state by in situ photoemission spectroscopy with Ar gas cluster ion beam sputtering. Issue 1 (11th December 2017) - Yun, Dong-Jin; Kim, Seyun; Jung, Changhoon; Lee, Chang-Seok; Sohn, Hiesang; Won, Jung Yeon; Kim, Yong Su; Chung, JaeGwan; Heo, Sung; Kim, Seong Heon; Seol, Minsu; Shin, Weon Ho
Abstract : We propose a novel, direct diagnosis method for graphene doping states at organic semiconductor/electrode interfaces by an in situ photoemission spectroscopy method. Abstract : On the basis of an in situ photoemission spectroscopy (PES) system, we propose a novel, direct diagnosis method for the characterization of graphene (Gr) doping states at organic semiconductor (OSC)/electrode interfaces. Our in situ PES system enables ultraviolet/X-ray photoelectron spectroscopy (UPS/XPS) measurements during the OSC growth or removal process. We directly deposit C60 films on three different p-type dopants—gold chloride (AuCl3 ), (trifluoromethyl-sulfonyl)imide (TFSI), and nitric acid (HNO3 ). We periodically characterize the chemical/electronic state changes of the C60 /Gr structures during their aging processes under ambient conditions. Depositing the OSC on the p-type doped Gr also prevents severe degradation of the electrical properties, with almost negligible transition over one month, while the p-type doped Gr without an OSC changes a lot following one month of aging. Our results indicate that the chemical/electronic structures of the Gr layer are completely reflected in the energy level alignments at the C60 /Gr interfaces. Therefore, we strongly believe that the variation of energy level alignments at the OSC/graphene interface is a key standard for determining the doping state of graphene after a certain period of aging.